Pengembangan Inovasi dan Utilitas Minyak Atsiri Lokal untuk Menguatkan Daya Saing dan Kemitraan: Indonesia - Rubiyanto, Dwiarso; Musawwa, Muhammad Miqdam; Prakoso, Nurcayo Iman; Rahmatillah, Cecep Sa'bana; Saputro, Matkli Dimas Astriyanto (Jurnal Abdimas Madani dan Lestari (JAMALI), 2026)
Currently, the development of local potential based on natural product and materials requires concrete steps to increase added value, stimulate investment and find new markets at home and abroad. One of the natural material commodities that has great potential is essential oil which is included in the plantation agribusiness sub-sector. So far, the essential oil industry has only maintain at the home industry and is still feeling the way in place. The study and development of techniques and knowledge about the benefits and applications of essential oils by involving research institutions both in the government and in universities has not been clearly known by most of the public. Essential oils produced by the Indonesian people are not yet popular even though in their daily lives the community is very close and even involved in the use of essential oil ingredients. Innovation and creation of essential oil derivative products involving various partners are new development challenges that must be faced by research institutions owned by universities and government-owned in order to jointly increase the nation's sustainable competitiveness. Center of Essential Oil Studies (CEOS UII) supports joint efforts between the government and the business sector even at the UMKM level so that technology dissemination takes place intensively and evenly, including the use of natural resources that are being innovatively developed and the diversification of the utilization of derivative and formulative products. Agribusiness and essential oil agroindustry business actors need to be used as partners so that the development of essential oil innovation and utility can be broad and even. Superior essential oil products need to be developed in suitable areas, using quality plant materials, and applying good cultivation methods to increase productivity and quality as well as variety of plant types. This activity will make one region produce superior and mainstay products that are highly competitive and give birth to partnerships that support each other and provide solutions to local and regional problems as quickly as possible. Indonesia's agro-industry and essential oil agribusiness are faced with two main problems, namely low quality and fluctuating prices. One of the solutions is an extensification and intensification program in the commodity and non-commodity sectors of essential oils. The essential crop extensification program needs to consider market absorption and prioritize the regional program of a region's mainstay commodity. The intensification program is prioritized to increase the productivity and quality of essential oil raw materials. This is intended so as not to pose a risk of loss for essential oil farmers.